Analysis of Lightweight Polystyrene Foam Concrete Flat Slabs under Fire Condition. (22nd June 2022) - Alzara, Majed; Riad, Magdy; AbdelMongy, Mohamed; Farouk, Mohamed A.; Yosri, Ahmed M.; Moubarak, Ahmed M.; Ehab, Ahmed
Abstract : Lightweight reinforced concrete (LWC) is widely used in various reinforced concrete (RC) applications, such as its use in diverse types of reinforced concrete slabs. The aim of this study is to analyze the behavior of reinforced foam concrete slabs (flat slab type) that are exposed to fire conditions under the influence of eccentric loads as well as concentric loads. This analysis has been done using the finite element method by a (ANSYS) software program. The validity of the adopted models was verified through comparison with a previous experimental study. The studied specimens were eleven reinforced concrete flat slabs with a thickness of 150 mm. The lightweight polystyrene foam concrete was used in these specimens with a density of 1820 kg/m 3 . The results showed that the fire effect lead to a decrease in the maximum carrying load of foam concrete slabs by 25%. Also, by comparing the finite element results with the selected experimental study, the results showed a great agreement with the analytical study used in this research.